المفاهيم الإسلامية في الأفلام الملايوية: فيلم "بنديكار بوجنج لابوق" من إخراج بي رملي نموذجا : Islamic concepts in Malay film: "Pendekar Bujang Lapok" directed by P. Ramlee as a Model - Abdul Razak, Muhammad Anas; Ahmad H. Osman, Rahmah; Mohd Tumiran, Dayang Alwani (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص يعتبر الفيلم وسيلة فعالة بشكل ملحوظ في تمثيل الواقع كما له دور بارز في استحضار المشاعر، كذلك يؤثر الفيلم أيضًا في تكوين شخصية المجتمع في هذا العصر، وبالنظر نرى أن هناك العديد من الأفلام التي تعطي الآثار السلبية في حياة المجتمع لأنها خلت من المفاهيم الإسلامية. حاول الباحث من خلال هذا البحث أن يبحث المفاهيم الإسلامية الموجودة في أحد الأفلام المشهورة في ماليزيا وتأثيرها في حياة المجتمع. وتهدف هذه الدراسة إلى إظهار المفاهيم الإسلامية التي احتوى عليها فيلم "بنديكار بوجنج لابوق". إذا عُرضت هذه المفاهيم من خلال محاور أحداث الفيلم. فجاءت هذه التساؤلات؛ عن ماهية هذه المفاهيم، وكيفية عرضها، والهدف من سرد هذا الفيلم لهذه المفاهيم وما الذي أراد مخرج الفيلم توصيله للمشاهد. وبالإضافة إلى ذلك، تهدف هذه الدراسة إلى تحليل تأثير هذا الفيلم على سلوك المجتمع.وقد اعتمد الباحث على المنهج الوصفي التحليلي في هذه الدراسة، كما استخدم الاستبانة كأداة رئيسية للحصول على المعلوملت والبيانات الأولية، إضافة إلى أداتي المقابلة والملاحظة كأدوات مساعدة. وقد أظهرت نتائج البحث أن هذا الفيلم يحتوي على بعض خصائص الحضارة الإسلامية الموجودة في أرض الملايو. بالإضافة إلى ذلك يحاول المخرج أيضًا إظهار القيم الإنسانية التي كانت موجودة بعد ظهور الإسلام في أرض الملايو. ويحاول المخرج كذلك إظهار مساهمة الحضارة الإسلامية في أرض الملايو وتأثيرها على سلوك المجتمع. Abstract Film is a remarkably effective medium in conveying drama and especially in the evocation of emotion. The film also affects the formation of society’s personality. In this era, there are many films that give negative effects in the life of the community because no Islamic concepts found in that films. The researcher tried to research Islamic concepts present in one of the famous films in Malaysia and their impact on the life of society. This study aims to show the Islamic concepts contained in the movie "Pendekar Bujang Lapok". If these concepts are presented through the axes of the events of the film. So, these questions came about what these concepts are, how they are presented, and the purpose of telling this film that the film director wanted to communicate to the viewer. In addition, this study aims to analyze the effect of this film on the behavior of society. The researcher adopted the descriptive analytical method and used interview and questionnaire as the research tools to get the necessary information and data, in order to achieve the objectives of the study. The results of the research found that this film contains some characteristics of the Islamic civilization found in the land of Malay. In addition, the director also tries to show the human values that existed after the advent of Islam in the land of Malay. The director tries to show the contribution of Islamic civilization in the land of Malay and its impact on the behavior of society.